Cytotoxic effects of hydro-ethanolic extracts from Coleostephus myconis (L.) rchb.f. flowers and green parts - Bessada, Silvia (2017)
The species Coleostephus myconis (L.) Rchb.f. is considered as being a harmful and persistent weed, with constant presence in abandoned farmland. Prevailing in the Portuguese flora, C. myconis belongs to the Asteraceae family, which is recognized for its global medicinal value and high antioxidant power, as described in different research works. Nevertheless, before considering incorporating this species in food of pharmaceutical applications, it is imperative to evaluate their potential toxicity.